2015
DOI: 10.1111/neup.12200
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic study of endolymphatic sac tumor (ELST) and differential diagnosis of papillary tumors located at the cerebellopontine angle

Abstract: We investigated the clinicopathologic features and immunophenotypes of 10 cases of endolymphatic sac tumor (ELST) and compared them with other papillary tumors, including eight cases of choroid plexus papilloma (CPP), three cases of atypical choroid plexus papilloma (ACPP), two cases of papillary ependymoma (PE), three cases of papillary meningioma (PM) and two cases of metastatic carcinoma (MC) the at cerebellopontine angle (CPA). The age at onset of ELST ranged from 13 to 39 years. The male-to-female ratio w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…The differential diagnosis histologically includes metastatic ccRCC, papillary thyroid carcinoma or follicular thyroid carcinoma, while choroid plexus papilloma, papillary ependymoma, papillary meningioma, paraganglioma and even middle ear adenoma are less frequently considered [56]. Centering of the tumors within the cerebellopontine angle, tumors with psammoma bodies and whorling, along with unique immunohistochemistry findings (such as CK5/6, synaptophysin, progesterone receptors) help to exclude the less common considerations of choroid plexus papilloma, papillary ependymoma and papillary meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis histologically includes metastatic ccRCC, papillary thyroid carcinoma or follicular thyroid carcinoma, while choroid plexus papilloma, papillary ependymoma, papillary meningioma, paraganglioma and even middle ear adenoma are less frequently considered [56]. Centering of the tumors within the cerebellopontine angle, tumors with psammoma bodies and whorling, along with unique immunohistochemistry findings (such as CK5/6, synaptophysin, progesterone receptors) help to exclude the less common considerations of choroid plexus papilloma, papillary ependymoma and papillary meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…Summarising information from 27 publications and our own data, genetic and clinical information of 158 VHL‐disease‐related ELSTs and 21 sporadic ELSTs was available (Table S4) [3, 6–11, 19–38]. VHL‐disease‐related ELSTs affected 31 females and 20 males (NA = 107), sporadic ELSTs 11 females and 10 males.…”
Section: Resultsmentioning
confidence: 99%
“…They may even expand into the posterior fossa representing a rare differential diagnosis for tumours of the cerebellopontine angle; e.g., Roche et al [2] found one ELST for every 300 vestibular schwannomas. They may be misdiagnosed as reactive and inflammatory processes, plexus tumours or metastases from thyroid, lung or clear cell renal carcinomas [1, 3–5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, particularly in patients with clinical manifestations simulating Ménière's disease, the endolymphatic sac region must be carefully examined in order not to miss an ELST [25]. ELSTs may be sporadic or associated with von Hippel-Lindau (VHL) disease which is attributable to inactivation of a tumor suppressor gene on the short arm of chromosome 3, and inherited as an autosomal dominant trait with variable expression [1,14,15,20,[26][27][28][29][30][31][32][33][34][35][36][37]. VHL predisposes patients to multiple hemangioblastomas of the retina or central nervous system as well as tumors and cysts in various organs, including renal cell carcinoma, pheochromocytoma, paraganglioma, ELST, epididymal cystadenoma, and pancreatic serous cystadenoma or neuroendocrine tumors [1].…”
Section: Clinical and Radiographic Featuresmentioning
confidence: 99%